Pellet Production by Cold Bonding and Low Temperature Bonding Methods (e14fb394-aca1-4ca9-bea4-663f2c3ca0bd) - H. Xi-Lum (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1984)
Three rapid cold bonding production methods wing sponge iron powder as a binder for low temperature pellets have been successfully developed. These methods differ from ordinary bonding by the elimination of salt and other catalyzers, equipment corrosion and environmental pollution. Experiments show that these pellets have good metallurgical properties. A semi-industrial test has proven the laboratory results, with the continuous and stable production of metallic pellets. These methods replace traditional high temperature firing of oxidized pellets for direct reduction. As a result, the plant for oxidized pellets can be saved and substituted for grate in the grate-kiln system. Thus, 20% of the investment could be saved, and production cost may also be decreased because the production of cold bonding pellets does not need additional space.